Causal structure and birefringence in nonlinear electrodynamics - Melo, C. A. M. de [UNESP]; Medeiros, L. G.; Pompeia, P. J. (World Scientific Publ Co Pte Ltd, 2015)
We investigate the causal structure of general nonlinear electrodynamics and determine which Lagrangians generate an effective metric conformal to Minkowski. We also prove that there is only one analytic nonlinear electrodynamics not presenting birefringence.
Keywords: Nonlinear electrodynamics; Effective metrics; Photon propagation